Local voices, global languages: Teachers’ perspectives on local-based digital narratives and multilingual practices in early EFL learners - Tri Pujiani; Hasan Zainuri; Ida Dian Sukmawati (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
The growing trend towards English-language education at earlier ages in multilingual societies demands a greater need to develop teaching strategies that are both culturally and linguistically responsive and developmentally appropriate. In this mixed-method research, this study aims to understand the perceptions of kindergarten teachers regarding the use of locally-based digital narratives and multilingual practices in EFL classes for early EFL learners. Data were collected through distributing questionnaires to early childhood EFL teachers, followed by semi-structured interviews with nine purposively selected participants. Data analysis was done quantitatively using descriptive statistics and qualitatively using thematic analysis. The findings indicate that teachers found locally-based digital narratives beneficial in increasing engagement and confidence among learners due to their association with real-world contexts. Furthermore, teachers felt that multilingual practices would help reduce anxiety levels and support comprehension and vocabulary learning. But teachers faced issues such as technological inadequacy and teacher training in implementing the above strategies in class. The study concludes that combining culturally grounded digital narratives with multilingual pedagogy holds significant promise for early EFL education and that providing institutional support is strengthened. These findings provide empirical insights into teachers’ perspectives and suggest implications for curriculum development and teacher professional learning in multilingual contexts.